Diseño de una unidad de gestión de energía para dispositivos médicos implantables con alimentación basada en transferencia inalámbrica de potencia por ultrasonido - Vilca Pizarro, Julio David (2024)
This thesis presents the design of a Power Management Unit (PMU) integrated circuit, intended for implantable medical devices (IMDs) powered by ultrasonic wireless power transfer. The design takes into account the specific constraints of IMDs, such as limited available power and the need for high efficiency to avoid thermal damage to surrounding tissue. The circuit was designed in a standard 0.18 μm CMOS technology from TSMC, and simulations were performed using Cadence software. The PMU design is based on an active rectifier composed of a core, two comparators, two buffers, a temperature-compensated current reference, and a voltage limiter. The core rectifier was designed using two PMOS transistors in a cross-coupled configuration and two NMOS transistors as active switches for AC to DC voltage conversion. The comparators were designed with a common-gate topology to generate the control voltage required for activating the active switches. These comparators, optimized to operate with a 1 μA bias current, achieve a gain of 48.37 dB, a unity-gain frequency of 221.8 MHz, and a PSRR of 48.22 dB. The buffers were designed with chains of four CMOS inverters in an exponential horn configuration to restore the comparator output voltage with minimal propagation delay. The temperature-compensated current reference, designed using a topology based on self-cascode composite transistors (SCCT), generates a 1 μA current with a temperature coefficient of 71.54 ppm/◦C and a line regulation of 9.14 nA/V, to supply the necessary bias current to the comparators. The voltage limiter was implemented using diode-connected transistors in antiparallel to protect the circuit from potential overvoltages exceeding 1.8 V. With a total power consumption of 21.7 μW, the PMU circuit achieves a power conversion efficiency (PCE) of 95.48% and a voltage conversion ratio (VCR) of 87.29%. Powered by a piezoelectric transducer model with a maximum available power of 524.7 μW, a frequency of 1.5 MHz, and an impedance of Zpiezo = 2.14 kΩ + j398.7 Ω, the PMU is capable of delivering a DC output power of 459.6 μW and a DC output voltage of 1.17 V to the load. The PMU circuit has demonstrated robust performance under extreme variations of process, voltage, and temperature conditions, and incorporating an external impedance matching network, it achieves a PCE of over 83.66% and a VCR exceeding 93.39% in the worst-case scenario.